Exploring the Laboratory Equipment Status in Public Remote Schools: Basis for a Strategic Laboratory Development Plan - Archie C. Madarang; Lilibeth G. Abrogena (Future Science / FSH-PH Publications, 2026)
This study looked into the status of laboratory equipment in the facilities of public remote secondary schools in the Schools Division of Ilocos Norte for the 2025–2026 academic year and in particular the lack of laboratory equipment. An inquiry of a case study research design using a mixed-methods method was carried out. Researchers recruited 50 science teachers from 20 distant secondary schools to participate in the study by using purposive and census sampling. An adapted survey questionnaire and checklist adapted from DepEd Order No. 118, s. 2009 the study purposely sampled teachers, comprising more than five years’ experience and related training, in science teaching. Descriptive statistics including frequency counts and percentage analyses, as well as thematic analysis, were employed to analyze data as described by Braun and Clarke (2016). The results of this study demonstrated the notable lack of primary laboratory materials, such that several of the key items were found to be totally missing in all the schools identified. In contrast, most studies found cheap laboratory materials that only served the regular tasks were available. Such deficiencies limit access to hands-on experimentation, real world experience and hands-on science lessons that impact students’ engagement and the acquisition of fundamental skills. Thus, the results underline a need for targeted interventions to supplement the provision of equipment, chemicals, and models not only to prepare teachers but also to reinforce science training within schools at a distance and assure students get an opportunity for laboratory training.